Effects of ACE Inhibitors and Angiotensin Receptor Blockers in Normotensive Patients with Diabetic Kidney Disease - He, Dandan; Zhang, Yaru; Zhang, Wei; Xing, Yue; Guo, Yipeng; Wang, Fuzhen; Jia, Junya; Yan, Tiekun; Liu, Youxia; Lin, Shan (Hormone and Metabolic Research, 2020)
The role of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) in reducing the progression of albuminuria and risk of cardiovascular events in hypertensive patients with diabetic kidney disease (DKD) is well-documented. However, the efficacy and safety of these agents in normotensive patients with DKD are still controversial. MEDLINE, Embase, and Cochrane Library were searched for relevant random controlled trials. The odd risk (OR) reductions were calculated with a random-effects model. Decrease in albuminuria, changes in eGFR, major cardiovascular events, and drug-related adverse events were analyzed. Thirteen RCTs including 1282 patients were retrieved. Compared with placebo or other active agent groups, ACEIs or ARBs significantly decreased albuminuria (MD –80.28 mg/d, 95% CI –104.79 mg/d to –55.77 mg/d), and the efficacy is independent of changes in blood pressure and systolic blood pressure at baseline. The result of subanalysis showed the declining of albuminuria was more significantly in normotensive DKD patients with 2DM (p=0.005). No significant differences were found with regard to the declining of evaluated glomerular filtration rate (eGFR) (MD –0.29 ml/min/1.73 m2, 95% CI –2.99 to 2.41 ml/min/1.73 m2). There were no significant differences in the side effect of the drugs such as hypotension and hyperkalemia. This meta-analysis demonstrated that ACEIs or ARBs can decrease albuminuria to varying degree in normotensive patients with DKD, and better response occurred in patients with 2DM.
Keywords: diabetic kidney disease; angiotensin-converting enzyme inhibitors; angiotensin receptor blockers; albuminuria; cardiovascular events; meta-analysis